Uterine and Hormonal Changes Following Pregnancy in Ruminants - Dina H. Sadiq (Academia Open, 2025)
General Background: Pregnancy is a pivotal phase in the reproductive cycle of mammals, particularly in ruminants, involving intricate physiological and hormonal coordination. Specific Background: Hormonal fluctuations during estrous, pregnancy, and parturition significantly influence uterine and endometrial structure, immune modulation, and mammary development. Knowledge Gap: Despite the known involvement of endocrine signaling, detailed insights into uterine transformations post-pregnancy and species-specific hormonal patterns remain limited. Aim: This review aimed to examine uterine changes in ruminants after pregnancy, focusing on the hormonal and immunological mechanisms involved.Results: It highlights how estrogen and progesterone modulate endometrial dynamics and immune responses; the trophoblast’s role in sustaining progesterone secretion through corpus luteum maintenance; and the regulatory cascade triggered by prostaglandin F2α in luteolysis. Notably, cows exhibited higher reproductive hormone levels compared to other ruminants. Novelty: The review integrates hormonal profiles with immune function and mammary gland development, offering a comprehensive picture of post-pregnancy uterine remodeling. Implications: These findings enhance understanding of implantation biology, support strategies to optimize reproductive efficiency, and inform sustainable dairy and meat production practices in ruminants Highlights: Hormones like progesterone and estrogen drive key uterine and immune changes. Trophoblast signals are crucial to sustain pregnancy in ruminants. Cows show higher reproductive hormone levels than other ruminants. Keywords: Uterine Remodeling, Ruminant Reproduction, Hormonal Regulation, Immune Response, Mammary Development